\(\left(x-1\right)^4-8\left(x-1\right)^2-9=0\)
\(\left[\left(x-1\right)^2\right]^2-2.\left(x-1\right)^2.4+16-25=0\)
\(\left[\left(x-1\right)^2-4\right]^2-5^2=0\)
\(\left[\left(x-1\right)^2-4-5\right]\left[\left(x-1\right)^2-4+5\right]=0\)
\(\left[\left(x-1\right)^2-9\right]\left[\left(x-1\right)^2+1\right]=0\)
\(\left(x-4\right)\left(x+2\right)\left[\left(x-1\right)^2+1\right]=0\)
\(\Rightarrow\orbr{\begin{cases}x-4=0\\x+2=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=4\\x=-2\end{cases}}\)
Đặt \(t=\left(x-1\right)^2\ge0\). Phương trình trở thành:
\(t^2-8t-9=0\) (1)
Để pt (1) có nghiệm thì \(\Delta_{\left(1\right)}=\left(-8\right)^2-4.\left(-9\right)\ge0\Leftrightarrow100\ge0\) (đúng vì 100 > 0)
Suy ra \(t_1=\frac{8+\sqrt{100}}{2}=9\left(C\right);t_2=\frac{8-\sqrt{100}}{2}=-1\left(L\right)\)
Thay t1 vào và ....
Note: Em không chắc ạ!
Đặt \(t=\left(x-1\right)^2\left(t\ge0\right)\)(1)
Thay (1) vô pt :
\(t^2-8t-9=0\)
\(\Leftrightarrow t^2+t-9t-9=0\)
\(\Leftrightarrow\left(t-9\right)\left(t+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}t=9\left(tm\right)\\t=-1\left(l\right)\end{cases}}\)
\(\Rightarrow\left(x-1\right)^2=9\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=3\\x-1=-3\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=4\\x=-2\end{cases}}\)
Vậy S={...}